Visualizing equality : African American rights and visual culture in the nineteenth century - Gonzalez, Aston, 1986- (John Hope Franklin series in African American history and culture., 2020)
"Visualizing equality ... analyz[es] how previously unexamined or understudied African American artists shaped conceptions of race during the nineteenth century. Marshaling material from 26 private and public archives in the United States and England, Gonzalez charts the changing roles of African American visual artists as they used their work to expand black rights in the United States. Understudied or forgotten artists such as Robert Douglass Jr., Patrick Henry Reason, James P. Ball, and Augustus Washington produced images to persuade viewers of the necessity for black social equality, political enfranchisement, and freedom from slavery, and Gonzalez argues that these cultural producers helped to make the world they envisioned through their art"--